2020
DOI: 10.3390/su12166673
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Automated Text Analysis of Airbnb Reviews in Hong Kong and Singapore Using Latent Dirichlet Allocation

Abstract: Airbnb has emerged as a platform where unique accommodation options can be found. Due to the uniqueness of each accommodation unit and host combination, each listing offers a one-of-a-kind experience. As consumers increasingly rely on text reviews of other customers, managers are also increasingly gaining insight from customer reviews. Thus, this present study aimed to extract those insights from reviews using latent Dirichlet allocation, an unsupervised type of topic modeling that extracts latent discussion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…To perform LDA and define the optimal number of topics, the authors evaluated the performance of different selections of K as the total number of topics. As suggested by Kiatkawsin et al (2020), the results of each method were normalised on a scale from 0 to 1 before the LDA models ran the results. It is worth noting that every possible number of topics between 2 and 50 was identified and scored through a grid search.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform LDA and define the optimal number of topics, the authors evaluated the performance of different selections of K as the total number of topics. As suggested by Kiatkawsin et al (2020), the results of each method were normalised on a scale from 0 to 1 before the LDA models ran the results. It is worth noting that every possible number of topics between 2 and 50 was identified and scored through a grid search.…”
Section: Methodsmentioning
confidence: 99%
“…The results of LDA showed that there are five aspects of the hotel: location, meal, service, comfort and cleanness, and concluded that the overall sentiment is influenced by one aspect. Kiatkawsin et al (2020) compared two rival destinations, Hong Kong and Singapore, using latent Dirichlet allocation. In their research, 185,695 from Hong Kong`s and 93,571 from Singapore`s Airbnb were analysed, and a total of twelve topics were identified for Hong Kong, which are be categorized into four different groups, while Singapore's optimal number of themes was only five.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experience and existing knowledge related to adventure activities were found to have significant influences on attitude [ 6 , 23 , 26 , 27 ]. Thus, attitude helps to determine the likelihood of participation in the activity [ 28 , 29 , 30 , 31 , 32 ]. Moreover, constructs such as sensation seeking and worry have been found to help in coping with the level of perceived risks usually associated with adventure tours [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Text classification refers to the process of categorizing textual data into a set of defined classes. Classical approaches to text classification rely on feature extraction techniques such as n-grams, Bagof-Words, and TF-IDF, a potential dimensionality reduction step, followed by learning a classification model such as Logistic Regression, Naive Bayes, Support Vector Machines, Latent Dirichlet Allocation, and Nearest-Neighbours algorithms (Kowsari et al, 2019;Kiatkawsin et al, 2020). More recently, deep-learning-based language models that are trained using contextualized word representations have been used to achieve state-of-the-art results on a wide range of natural language benchmarks and datasets, including text classification (Devlin et al, 2019;Lewis et al, 2020;Minaee et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%